Electric Motorbike Conversion Training to Reduce Pollution and Create A Friendly Environment For Society - Appin Purisky Redaputri; Aprinisa Aprinisa; Niki Agus Santoso (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2024)
Electric motorbike conversion training at Vocational High Schools (SMK) and motorbike workshops in Kotabumi, North Lampung, is a strategic step to prepare future workers to face the electricity-based transportation revolution. This study aims to evaluate the impact of training on improving the technical skills of vocational school students and motorbike repair shop mechanics, as well as analyzing the contribution of training to the adoption of environmentally friendly technology at the local level. The training method includes theoretical exposure, field practice sessions, and case studies to provide an in-depth understanding of electric motor conversion. Evaluation is carried out through practical exams and collecting feedback from participants and instructors. The research results showed a significant increase in participants' knowledge and skills regarding electric motor conversion. Adoption of this technology in local motorbike workshops is also increasing, creating the potential for reduced environmental impact and generating positive effects on the local automotive industry. The conclusion confirms that this training was successful in empowering vocational school students and motorbike repair mechanics, creating new career opportunities, and stimulating economic growth in the region. However, challenges such as adapting infrastructure and changing mindsets were also identified as areas requiring further attention. Therefore, this research provides valuable insights for further development in supporting technical education, industrial innovation and sustainability at the local level.